Sex Differences in US Army Suicide Attempts During the Wars in Iraq and Afghanistan - Naifeh, James A. (Med Care, 2021)
To examine sex differences in risk for administratively documented suicide attempt (SA) among US Army soldiers during the Iraq/Afghanistan wars. METHOD: Using administrative person-month records of Regular Army enlisted soldiers from 2004 to 2009, we identified 9650 person-months with a first documented SA and an equal-probability control sample (n=153,528 person-months). Person-months were weighted to the population and pooled over time. After examining the association of sex with SA in a logistic regression analysis, predictors were examined separately among women and men. RESULTS: Women (an estimated 13.7% of the population) accounted for 25.2% of SAs and were more likely than men to attempt suicide after adjusting for sociodemographic, service-related, and mental health diagnosis (MHDx) variables (odds ratio=1.6; 95% confidence interval, 1.5–1.7). Women with increased odds of SA in a given person-month were younger, non-Hispanic White, less educated, in their first term of enlistment, never or previously deployed (vs. currently deployed), and previously received a MHDx. The same variables predicted SA among men. Interactions indicated significant but generally small differences between women and men on 6 of the 8 predictors, the most pronounced being time in service, deployment status, and MHDx. Discrete-time survival models examining risk by time in service demonstrated that patterns for women and men were similar, and that women’s initially higher risk diminished as time in service increased. CONCLUSIONS: Predictors of documented SAs are similar for US Army women and men. Differences associated with time in service, deployment status, and MHDx require additional research. Future research should consider stressors that disproportionately affect women.